2018
DOI: 10.3390/en11102655
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Model for Performance Analysis of a Stirling Engine Prototype

Abstract: In this study, the results of simulations generated from different thermodynamic models of Stirling engines are compared, including characterizations of both instantaneous and indicated operative parameters. The aim was to develop a tool to guide the decision-making process regarding the optimization of both the performance and reliability of Stirling engines, such as the 2.9 kW GENOA 03 unit—the focus of this work. The behavior of the engine is characterized using two different approaches: an ideal isothermal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
(32 reference statements)
2
12
0
Order By: Relevance
“…• C up to maximum tested level (6 bar) for 400 • C. It can be concluded that further rise of charge pressure should simultaneously increase the indicated work produced by the engine for 350 as well as Energies 2020, 13, 1622 6 of 21 400 • C. Unfortunately, the sealing system used in the prototype engine is not suitable for such a level of pressure. The increase of the indicated work, due to heating temperature rise, is in line with the theoretical description of a Stirling engine cycle [22][23][24], the higher temperature difference between upper and lower heat source, the higher efficiency of the engine, which means more work for the given thermal energy impact. The effect of rising efficiency is, at the same time, amplified by the increase of thermal energy transmitted by the heater to the working gas, which comes also from the higher heating temperature.…”
Section: Engine Performancesupporting
confidence: 75%
See 3 more Smart Citations
“…• C up to maximum tested level (6 bar) for 400 • C. It can be concluded that further rise of charge pressure should simultaneously increase the indicated work produced by the engine for 350 as well as Energies 2020, 13, 1622 6 of 21 400 • C. Unfortunately, the sealing system used in the prototype engine is not suitable for such a level of pressure. The increase of the indicated work, due to heating temperature rise, is in line with the theoretical description of a Stirling engine cycle [22][23][24], the higher temperature difference between upper and lower heat source, the higher efficiency of the engine, which means more work for the given thermal energy impact. The effect of rising efficiency is, at the same time, amplified by the increase of thermal energy transmitted by the heater to the working gas, which comes also from the higher heating temperature.…”
Section: Engine Performancesupporting
confidence: 75%
“…For example, between the heater -expansion spaces, during the flow from the expansion space the temperature is lower, and during the flow from the heater, the temperature is higher and corresponds to that in the heater. On this basis, the adiabatic work has been calculated (19) and, after taking pumping loss (22) into account the net adiabatic work (23) has been also calculated. For further considerations regarding the impact of selected design features of the system on the efficiency and power, the authors decided to use the simplified characteristics of the regenerator effectiveness taking into account only the effect of charge pressure:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulation work enables detailed study of Stirling engine design parameters [5]. It is used for the task of optimization [6 -13], exploration of new design or concept [14 -19] as well as parametric study of Stirling engines [5,20,21]. Experimental study focuses on validation and performance testing of existing or new Stirling engine design [9,16].…”
Section: Introductionmentioning
confidence: 99%